Deforestation-induced the EKC framework: The role of corruption control and trade openness in Southeast Asia - Destiartono, Mohamad Egi; Ekananda, Mahjus (Jurnal Ekonomi & Studi Pembangunan, 2023)
Reducing the deforestation rate and formulating sustainable forest governance are still challenging for Southeast Asia. This empirical research intends to explore the dynamic connection between GDP, trade openness, corruption, and deforestation within the EKC framework by considering controls over agriculture and population. This article uses panel data from nine countries from 1996 to 2018. Pooled Mean Group (PMG) procedure and Dumitrescu-Hurlin (DH) causality tests were applied to examine the variables’ long-term relationships and the direction of the causality. This article also features the unit root and cointegration tests. The estimation supports the EKC hypothesis that the nexus between economic growth and deforestation forms an inverted-U curve. The turning point of the per capita GDP is USD 26785, i.e., the advanced stage of development. Other findings are that trade openness is a driver of deforestation, while control of corruption is an effective instrument to reduce the deforestation rate in the long run. Deforestation will still occur in Southeast Asia because only Brunei Darussalam has passed the turning point. However, implementing development programs while reducing the deforestation rate can be done because the bidirectional causality between GDP and deforestation is not confirmed. Improving trade regulations and governance is a necessary scheme to reduce deforestation rates in the future.